Avaliação da qualidade nutricional, funcional e espectroscopia da farinha da pupunha (Bactris gasipaes Kunth) - DUARTE, Samanta de Paula de Almeida (2023)
The pupunha (Bactris gasipaes Kunth) is a species with high nutritional and functional value, its composition is rich in bioactive compounds. The objective of this work is to evaluate the nutritional, functional and technological potential of the flour of the pupunha (Bactris gasipaes Kunth) in order to promote the increase of raw materials for the various food segments. The methodologies applied followed the standards accepted by the Association of Official Analytical Chemists (AOAC). The results presented showed significant values in the nutritional aspect, with emphasis on macronutrients in lipid and protein, vitamin C, besides its potential as pro vitamin A. Regarding the evaluation of its technological potential, a raw material with high water absorption capacity, oil and emulsifying activity is showing that the application of the peach palm meal can be used as a base or proportional component as a mixture in the formulation of foods. Infrared spectroscopy shows the presence of positional bands around 900 cmˉ¹ and 300 cmˉ¹ ratifying the functional quality of a byproduct with unsaturated fatty acid residues. In view of the above, we can verify the importance of knowledge of new matrices, the flour of pupunha evidenced a high degree of nutritional, functional and technological aspects, making it a raw material with a high benefit for human nutrition.